1995
DOI: 10.1007/bf00203687
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging diagnosis of an aortocoronary saphenous vein graft aneurysm

Abstract: Magnetic resonance imaging (MRI) allowed the diagnosis of an atherosclerotic aneurysm of a long-standing aortocoronary saphenous vein graft, initially not depicted by selective coronary graft arteriography due to low flow within the lumen, caused by a stenosis of the proximal graft limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…The latter is particularly useful in identifying saphenous vein graft aneurysms in which coronary angiography was of limited value owing to proximal stenosis and insuf®cient¯ow [9].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them have been observed in old saphenous SVG [1,2,3]. These aneurysms may disturb the graft function and cause recurrent angina [4] or non-Q myocardial infarction [5], requiring surgical reintervention [4,6,7], which is sometimes fatal in these elderly patients with multiple-organ dysfunctions [4].…”
Section: Introductionmentioning
confidence: 99%